Eksil Banten dan Terbentuknya Komunitas Muslim di Minahasa Abad XIX - Kembuan, Roger Allan Christian (Jurnal Sejarah Indonesia, 2024)
This article discusses the socio-cultural life and development of the exiled Muslim community from Banten in the Minahasa Residency, which was a location for exile in line with the Dutch colonial government's policy of placing exiles from Banten in the Manado (Minahasa) Residency throughout the 19th century. The historical method used in this research is by using the 19th century Colonial Archives stored in the National Archives of the Republic of Indonesia, travel reports, and local sources, especially manuscripts kept by their descendants in Tomohon and Minahasa. The findings in this research are: First, who are the figures from Banten who were exiled in Minahasa. Second, the reason Minahasa was chosen as the location of exile for the Dutch Colonial Government. Third, the form of adaptation carried out by the exiled community in Sarongsong village, Minahasa, Java. fourth, what is the relationship between Islam and Christianity after the arrival of exiles from Banten in Manado and Minahasa.